Effect of Telehealth System on Glycemic Control in Children and Adolescents with Type 1 Diabetes - Esra Döğer; Rukiye Bozbulut; A. Şebnem Soysal Acar; Şebnem Ercan; Aylin Kılınç Uğurlu; Emine Demet Akbaş; Aysun Bideci; Orhun Çamurdan; Peyami Cinaz (JCRPE, 2019)

(untitled)
Objective:A close diabetes team-patient relationship is required for establishing satisfactory metabolic control. The purpose of this study was to investigate the effect of a telehealth system on diabetes control.Methods:The study was carried out between June 2015 and January 2016 at the Gazi University Faculty of Medicine, Pediatric Endocrinology Department. The telehealth system was developed by the diabetes team. The demographic characteristics, frequency of use and hemoglobin A1c (HbA1c) changes of type 1 diabetic (T1DM) patients using this communication network were analysed.Results:Eighty two patients [43 (52.4%) females, mean (±standard deviation) age 10.89±4 years] used the telehealth system. Fourteen (17.1%) of the cases were on pump therapy and 59 (72.0%) were counting carbohydrates. The individuals with diabetes or their families preferred WhatsApp communication. Whatsapp provided a means for instant messaging in most instances (57.3%), contact with diabetes education nurse (32.9%) and consultation with the diabetes team about insulin doses and blood glucose regulation (42.7%). HbA1c values after six months were significantly lower in patients/parents calling frequently (p<0.001) compared with HbA1c values recorded at the beginning of the study.Conclusion:Increase in frequency of counselling by the diabetes team led to improved blood glucose control in T1DM patients. A telehealth system is useful for early detection of the need for changes in treatment and for intervention. It also promoted better self care.